The Truth of the Hadith about the Reasons for the Revelation of Surah Al-KÄfirÅ«n and Its Effect on Religious Tolerance - Rohmansyah, Rohmansyah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Hadithâ€™s authenticity on crucial things, such as tolerance in Surah Al-KÄfirÅ«n, must be studied. This paper aims to reveal and prove the status of the hadith as evidence of the revelation of Surah Al-KÄfirÅ«n, associated with religious tolerance. This study belongs to library research implementing a descriptive-analytic approach and a theoretical framework of the Sociology of Knowledge by Peter L Berger and Thomas Lukmann. The results unveiled that the hadith concerning the revelation of Surah Al-KÄfirÅ«n cannot be used as evidence because it was daif and mawquf. However, the tacitan of the hadith did not weaken the validity of the surah, of which the status is the word of God, which is qaá¹â€™Ä«. Therefore, Al-KÄfirÅ«nâ€™s correlation with religious tolerance remains valid as long as it pays attention to the determined limits. Mutual respect, assistance, and cooperation among religious people of different beliefs, and things unrelated to ideological aspects such as aqidah, worship, and sharia must be considered.The descent of suratÂ al-KÄfirunÂ exerts aÂ considerable influence onÂ the religiousness of the people. Every human being isÂ freeÂ to choose his religionÂ according to his beliefsÂ and their own beliefs. But especially MuslimsÂ haveÂ rulesÂ thatÂ stickÂ to their religion, as well asÂ non-Muslims. Mereka isÂ freeÂ to performÂ worshipÂ according to his understandingÂ andÂ belief. Surat al-KÄfirÅ«nÂ in addition toÂ teaching pluralityÂ inÂ religionÂ alsoÂ teaches the attitude of maintainingÂ unityÂ and unity ofÂ the people,Â reducingÂ hostilityÂ andÂ eliminatingÂ violenceÂ and panaticÂ againstÂ other groups. The majesty ofÂ suratÂ al-KÄfirÅ«n became aÂ wayÂ out of the problemÂ ofÂ conflictÂ betweenÂ religiousÂ peopleÂ since its descentÂ untilÂ now so thatÂ betweenÂ religiousÂ peopleÂ live get along wellÂ andÂ don'tÂ bother each other.Â